ANALISIS SISTEM PENGENDALIAN INTERNAL TERHADAP FUNGSI PENERIMAAN KAS PADA RUMAH SAKIT ORTHOPEDI DAN TRAUMATOLOGI SURABAYA - Yulianita Rochmana Pratiwi; Hero Priono (Universitas Sains dan Teknologi Komputer, 2021)
The purpose of this research is to analyze the internal control system in Orthopedic and Traumatology Hospital of Surabaya by comparing it with the internal control system brought up by COSO (Committee of Sponsoring Organizations). The research method used in this study is qualitative interpretive paradigm describing and understanding the events that occured based on the perspective and experiences of the subject researched directly. The data in this research are collected through interviews, direct observations to the research object and documentation. The results of the analysis and research shows that the internal control system on cash receipts in Orthopedic and Traumatology Hospital of Surabaya is quite effective. This is shown by the elements of internal control set in the hospital. This can be proven with the existence of forms which have been numbered and proofs of transactions are printed with three copies each and always verified. However there are still some concurrent duties and cash adjourment to the bank. Keywords: Internal Control System, Cash Receipts